Pathogenic variability and vegetative compatibility among isolates of Colletotrichum graminicola and C. gloeosporioides causing foliar and grain anthracnose in sorghum - and V.P. RA02, KUSUM MATHUR1, R.P. THAKUR2 (Indian Phytopathology, 2002)
Colletotrichum graminicola and C. gloeosporioides [Glomerella cingulata] cause foliar and grain anthracnose of sorghum. Foliage infection is more widely prevalent, but at times, grain anthracnose occurs in severe form. To understand whether isolatesinfecting foliage (lamina and midrib) and that infecting grain are different, isolates from foliage and grain were compared for pathogenicity and vegetative compatibility. In greenhouse experiments, isolate x host differential interaction was highly significant, indicating isolate specificity for infection to grain and foliage. Five popular sorghum hybrids also exhibited variable reactions to foliar and grain isolates. The results suggest that although the isolates from grain, leaf lamina and midrib can infect both foliage and grains, the organ specificity for infection does exist, and that resistance to grain and foliar infection is likely to be governed by different genetic factors. The isolates also varied in developing nitrate non-utilizing (nit)mutants on chlorate media and were identified in different vegetative compatibility groups. The isolates of C. graminicola were different from those of G. cingulata both for pathogenicity and vegetative compatibility.